2011
DOI: 10.1007/s11046-011-9510-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Prototheca zopfii Associated with Outbreak of Bovine Clinical Mastitis in Herd of Beijing, China

Abstract: Prototheca zopfii (P. zopfii) has become an important cause of bovine mastitis in many countries. In the present study, to better understand the occurrence of one clinical mastitis (CM) outbreak due to P. zopfii, the molecular characterization and resistance patterns of the microalga were described. P. zopfii strains were isolated from 17 of 23 quarters, which suffered CM in the outbreak, and 7 of 46 CM recovered quarters before the outbreak, as well as 2 of 75 environmental samples in the dairy farm. All stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 22 publications
10
48
0
Order By: Relevance
“…The results presented by Milanov et al (17) were comparable; all algae isolated from milk were also unsusceptible to enrofloxacin, amoxicillin, tetracycline, penicillin, lincomycin, and novobiocin. The obtained findings revealed that the highest antimicotic activity was demonstrated by nystatin, ketoconazole, and amphotericin B, which is consistent with the results of other authors confirming a high effectiveness of nystatin and amphotericin B against algae isolated from milk of mastitis-affected cows (5,7,14,17). Moreover, the results reported by Malinowski et al (10) were similar.…”
Section: Discussionsupporting
confidence: 89%
“…The results presented by Milanov et al (17) were comparable; all algae isolated from milk were also unsusceptible to enrofloxacin, amoxicillin, tetracycline, penicillin, lincomycin, and novobiocin. The obtained findings revealed that the highest antimicotic activity was demonstrated by nystatin, ketoconazole, and amphotericin B, which is consistent with the results of other authors confirming a high effectiveness of nystatin and amphotericin B against algae isolated from milk of mastitis-affected cows (5,7,14,17). Moreover, the results reported by Malinowski et al (10) were similar.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, beds for cows in the detached sand-floored cowshed were in ideal conditions for the development of algae and mammary gland infections via the galactogenic route. Similar environmental conditions favouring the development of protothecal mastitis were described by other authors (8,11,12,27). However, some authors (5, 9) did not isolate Prototheca sp.…”
Section: Discussionsupporting
confidence: 82%
“…The two remaining species, i.e. P. wickerhamii and P. blaschkeae, sporadically cause mastitis in cows (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…zopfii genotype 1 has only been isolated from the environment (27,28). In contrast, P. zopfii genotype 2 causes bovine mastitis and fatal systemic infection in dogs and has recently become a major concern worldwide (29)(30)(31)(32)(33)(34). In Germany and the United States, P. zopfii accounts for 20z-70z of bovine mastitis cases, and the proportion of infected cattle in Japan has been increasing (6,35,36).…”
Section: Introductionmentioning
confidence: 99%